Causes of shortness of breath in patients with stable coronary heart disease - S. F. Yarmedova; I. S. Yavelov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Shortness of breath is a common debilitating and limiting the quality of life symptom, which leads to frequent requests for medical help. The review summarizes data on the causes of shortness of breath in stable patients with suspected coronary heart disease (CHD), with an established diagnosis of CHD, as well as in patients with other cardiovascular diseases. PubMed, Science Direct, Google Scholar, and eLibrary search platforms were used for the selection of publications, the review includes publications from 2009 to 2021. Patients with suspected coronary artery disease complaining of shortness of breath, in addition to myocardial ischemia, not always associated with stenosing atherosclerosis of the coronary arteries. The following causes of shortness of breath are described: bronchial obstruction, psychogenic hyperventilation, and depression. When studying patients with other cardiovascular diseases, the causes of shortness of breath turned out to be even more diverse: transient myocardial ischemia (including in cases where the cause of shortness of breath initially appears to be non-ischemic), chronic heart failure, cardiac arrhythmias, pathology of the heart valves, thyroid dysfunction, lung diseases, obesity, anemia, etc. Thus, despite the limited evidence, it is obvious that in the presence of paroxysmal dyspnea in patients with stable coronary heart disease, its causes are more diverse than transient myocardial ischemia.